(untitled) (Aletria: Revista de Estudos de Literatura, 2008)
Resumo: Este trabalho investiga as possibilidades de uma literatura que trabalha com “restos do real”, analisando práticas de escrita experimentadas desde os anos 1970, na Argentina e no Brasil. Palavras-chave: poesia brasileira; ficção brasileira; ficção argentina. Abstract: This paper examines the possibilities of a literature that works with the “remains of the real”, analyzing experimental literary practices since the 1970s in Argentina and Brazil. Keywords: Brazilian poetry; Brazilian fiction; Argentinean fiction.